Meditation: A Double-Edged Sword—A Case Report of Psychosis Associated with Excessive Unguided Meditation - Goud, Sripathi Santhosh (Case Reports in Psychiatry, 2022)
Meditation is gaining a lot of popularity nowadays because of the associated benefits on both mental and physical health. There is ample literature available on the benefits of meditation. However, there are cases of psychosis reported sporadically in individuals who indulge in excessive unguided meditation. Herein, we report a patient who presented with schizophrenia after doing excessive meditation.